Uji Pengaruh Modal Intelektual terhadap Kinerja Keuangan BUMN yang Go Public di Indonesia - Ciptaningsih, Tri (SBM ITB, 2013)
This study examined the influence of intellectual capital on firm performance. The sample used in this study is that State-Owned Enterprises listed in Indonesia Stock Exchange for period 2007-2011. The test result based on multiple regression analysis indicated that: 1) VAIC has no effect on corporate performance, 2) HCE has no effect on corporate performance, 3) SCE has positive effect on corporate performance, 4) CEE has positive effect on company performance, 5) VAIC last year did not affect the company's performance today, 6) HCE last year did not affect the company's performance today, 7) SCE last year did not affect the performance of the company today, and 8) CEE last year has positive influence on the performance of the company today.Keywords: Intellectual capital, VAIC, human capital, structural capital and financial performance.